A REPORT OF EXPERIENCE ON THE ASSESSMENT OF PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION: THE USE OF ICONOGRAPHIC SOURCES AS ASSESSMENT TOOL IN THIS PROCESS (Fiep Bulletin - online, 2012)
Refers to a study carried out in Vila Velha, Espírito Santo, during the Supervised Degree in Physical Education as part of an institution of Early Childhood Education. Consider the stage as a time when the student approaches the reality and as a theoretical activity, exploited the teaching practice. Analyzes the contribution of the use of iconographic records (photos) as assessment tool in physical education classes in the kindergarten and identifies the importance of evaluation in the teaching and learning in this context. Points to the need to overcome the evaluation that shows the prospect of control over children's behavior and an ideal model of a child. Registers main study questions: 1) Characteristics of evaluation in physical education classes in the context of early childhood education, 2) The contribution of evaluation that focuses on the student as the subject and their effective participation in the evaluation process, prospects for qualification of the teaching process and learning and 3) The use of iconographic record as a means to perform the assessment in Early Childhood Education. It is a qualitative research refers to an experience report outlining dialogue with production in the area of ??Education and Physical Education and shows how key considerations: the use of the photo as possible to promote an evaluation to look beyond the motor , to assess the seizure, by the children, the area of ??knowledge inherent in the conceptual and attitudinal, the child's participation as a subject in the evaluation process, with opportunities for the pursuit of the development of child's autonomy and processes of self- evaluation, and self-evaluation through the iconographic record of the child as an opportunity to participate, analyze and express opinions in relation to physical education classes experienced in Early Childhood Education.
Keywords: early childhood education; assessment of learning; iconographic sources.